NAVIGATING THE INNOVATION LANDSCAPE: THE CRUCIAL ROLE OF TECHNOLOGY AND ENTREPRENEURIAL ORIENTATION - Riza, Fahrul; Luhur, Novia Agatha (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study examines the impact of technology orientation on entrepreneurial orientation and its consequent effect on the innovation performance of Indonesian startups. In this study, 156 local startups were examined using the structural equation model (SEM). The results demonstrate a significant and positive relationship between innovation performance and both entrepreneurial and technology orientation. Notably, the technology orientation has a positive effect on the entrepreneurial orientation, which partially mediates the indirect relationship between the technology orientation and innovation performance. This study's integrated framework concept to enhance the innovation performance of startups in emerging economies is unprecedented. The findings also urge businesses to adopt proactive, inventive, and risk-taking practices to keep up with the rapid pace of technological advancements. Certain limitations of this study must be acknowledged, including the subjective evaluation of constructs by senior management and the deliberate selection of the sample. To advance this topic further, it is suggested that future research include objective data gathered through assessments by various stakeholders and investigate case studies of designated businesses.JEL: L25, l26, O32.